Path Modelling of Interest in Entrepreneurship Programme, Intention to Start New Business and Employability skills among University Students - AKINTELU, S. Olufemi; ADEGBITE, W. Mulero (Covenant Journal of Entrepreneurship, 2024)
The problem that was addressed in this study was how the NUC entrepreneurship curriculum impacted student knowledge to become successful entrepreneurs after graduation to enhance economic growth in Nigeria. Cross-sectional research design was used for this study, and undergraduate students were the unit of analysis. Students that had participated in entrepreneurship programme organized by the university constituted the target population. This study was designed to assess whether entrepreneurship education enhances graduate employability. In other to test the hypotheses raised, the study used a sample of 145 undergraduates students drawn from fourteen (14) departments in three faculties of Samuel Adegboyega University, Nigeria. Data obtained was analyzed using path modelling to test the hypothesized model. Findings from the structural model assessment indicate that Students interest in entrepreneurship positively and directly affects their intention to start new business. Thus, a positive and significant relationship between interest in entrepreneurship programme and intention to start a new business among the sampled students. This implies that every time a student show interest in entrepreneurship training, it increases the students’ intention of starting a new business by 29%. Furthermore, the structural assessment further revealed that showing interest in entrepreneurship programme by the students enhances their employability skills. Consequently, the two hypotheses tested in this study were accepted.